Tehnični dejavniki aplikacije intramuskularne injekcije - Vehar, Aleš (Obzornik zdravstvene nege, 2021)
Introduction: Intramuscular injection is the most commonly used method of injection. The purpose of the study was to examine the latest findings in the field of site preparation and application of intramuscular injection. Methods: A systematic review of the scientific and professional literature was performed in the international databases CINAHL, PubMed, Cochrane Library and ScienceDirect. The following keywords were used: intramuscular injection, intramuscular vaccination, injection site, skin disinfection, injection technique. Boolean operators AND and OR were used in the search. The literature search was conducted in March and April 2021.Results: Of the 4208 search results, 13 articles were included in the final analysis. The findings were grouped into 4 categories: (1) puncture site selection, (2) intramuscular injection techniques, (3) disinfection of the puncture site and (4) aspiration. Discussion and conclusion: There is no common agreement regarding a safe and professional application of intramuscular injection among the authors of the reviewed studies. Research shows that the most suitable site of application is the ventrogluteal area. Disinfection of the puncture site before application is not necessary out of hospital, while aspiration is recommended only at the dorsogluteal site. The optimal application technique is the skin traction – pressure – rapid muscle release technique with selecting an appropriate needle size taking into account the thickness of the subcutaneous fat, the site of application and the density of the drug. Additional research should be conducted to unify the recommendations for the optimal intramuscular injection technique.
Keywords: adults; cepljenje; intervencija; intervention; mišica; muscle; odrasli; parenteral application; parenteralna aplikacija; vaccination